2021
DOI: 10.1136/sextrans-2020-054695
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisandMycoplasma genitaliumprevalence and associated factors among women presenting to a pregnancy termination and contraception clinic, 2009–2019

Abstract: BackgroundRisk of pelvic inflammatory disease associated with Chlamydia trachomatis and Mycoplasma genitalium is increased after termination of pregnancy (TOP) and may be increased after insertion of intrauterine devices (IUDs). Screening prior to these procedures is recommended only for C. trachomatis. We examined C. trachomatis and M. genitalium prevalence and associated factors among women presenting to a pregnancy termination and contraception service over 10 years.MethodsRetrospective analysis of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
7
1
1
Order By: Relevance
“…8,13 In women, young age, with a low education level, originating from sub-Saharan Africa, having ≥6 sexual partners in the last 6 months, onset of sexual activity after 20 years of age, HIV positivity, and co-infection with other STIs have been associated with a higher risk of having M. genitalium infection. 8,13,24 In our study having a partner experiencing symptoms of STIs was significantly associated with M. genitalium infection ( p < 0.05). Additionally, in the unadjusted analysis, having a partner who was experiencing symptoms of STIs increased the risk for infection by close to 4-fold (odds ratio (OR): 3.56, 95% confidence interval (CI): 1.14–10.59, p = 0:023) .…”
Section: Discussionsupporting
confidence: 47%
“…8,13 In women, young age, with a low education level, originating from sub-Saharan Africa, having ≥6 sexual partners in the last 6 months, onset of sexual activity after 20 years of age, HIV positivity, and co-infection with other STIs have been associated with a higher risk of having M. genitalium infection. 8,13,24 In our study having a partner experiencing symptoms of STIs was significantly associated with M. genitalium infection ( p < 0.05). Additionally, in the unadjusted analysis, having a partner who was experiencing symptoms of STIs increased the risk for infection by close to 4-fold (odds ratio (OR): 3.56, 95% confidence interval (CI): 1.14–10.59, p = 0:023) .…”
Section: Discussionsupporting
confidence: 47%
“…24 Many authors report this symptom as one of the most frequent in active CT infection. 5,25,26 However, according to our findings, this symptom was not associated with positive serology, probably because the majority of patients with positive IgG did not have an acute CT infection. IgG positive results were more frequently detected in women who reported having two or more pregnancies, and they were also associated with symptoms and signs related to lower genital infections, such as lower abdominal pain, genital odour and cervicitis.…”
Section: Discussionmentioning
confidence: 43%
“…In a retrospective study from 2009 to 2019, the detection rate of M. genitalium was 3.4% among 17,573 women who presented a pregnancy termination and contraception clinic, with the highest prevalence of 5.4% among 20–24 years. The prevalence fluctuated over time, from 4.4% in 2009 to 2.1% in 2013 and 4.8% in 2019 ( Shilling et al, 2022 ). A meta-analysis revealed that the prevalence of M. genitalium in the general population of developed countries was 1.3%, lower than 3.9% in underdeveloped countries, and the prevalence of sex workers was as high as 15.9% ( Baumann et al, 2018 ).…”
Section: Mycoplasma Genitalium and The Female Reproductive S...mentioning
confidence: 99%
“…A study in California showed that the co-infection rate with M. genitalium and C. trachomatis was 3.1% in women and 9.7% in men ( Getman et al, 2016 ). A study of the prevalence of C. trachomatis and M. genitalium among women attending termination of pregnancy and contraception clinics during 2009–2019 showed a co-infection rate of 10.1% for C. trachomatis and M. genitalium ( Shilling et al, 2022 ). In a recent HIV pre-exposure prophylaxis (PrEP) demonstration trial involving 200 men, molecular testing for N. gonorrhoeae , C. trachomatis , and M. genitalium found significantly higher gonococcal bacterial loads in the presence of M. genitalium , suggesting that M. genitalium may be a cofactor for N. gonorrhoeae transmission.…”
Section: Mycoplasma Genitalium and The Female Reproductive S...mentioning
confidence: 99%